A Midwife: Professional Ethics in Midwifery Practices, Managing Pregnancy and Childbirth Complications, and Legal Rights for Nursing Mothers - Ayesha Hendriana Ngestiningrum; siska diana sari; Rizka Rizka; Taadi Taadi; Sofyan Wimbo agung Pradnyawan; Sigit Sapto Nugroho; Dewi Iriani (Journal of Global Pharma Technology, 2020)
This study aims to discuss a midwife as a health professional, professional ethics in midwifery practices, the management of pregnancy and childbirth complication, and legal rights for nursing mothers. This qualitative research utilizes interview as a main instrument. The data are collected from interviews conducted with: 1.) pregnant women who gave premature birth, 2.) nursing women and families supporting breastfeeding program, and 3.) Public Health Office staffs. The study reveals that legal ethics between midwives and patients is significantly crucial. There is a need for effective communication between midwives and patients. Patients have the right to obtain information as clearly as possible and midwives also have the right to get the trust of patients to perform medical procedures without any interventions. In addition to the aforementioned result, this study reports that there is pregnancy and premature childbirth complication. It is a maternal health issue occurred during pregnancy causing premature birth. This study also highlights a breach of guarantee to nursing mothers who breastfeed up to 2 years of age. The results of study conclude three points. First, it reports informed consent. It is a process for getting permission before conducting a healthcare intervention on a person, or on disclosing personal information. Second, legal practice regulating rights for nursing mothers and its legal sanctions for someone who prohibits breastfeeding for working women or health workers who provide formula milk to newborns without medical indication. Third, the authorized party will conduct an investigative audit of cases of complications of pregnancy and childbirth that cause infant mortality.